Influence of Legal Environment and Banking System on Trade Credit in Private Firms - González, Víctor M. (Journal of business finance & accounting, 2025)
ABSTRACT Using a firm‐level database covering 52 countries during the period 2004–2021, I investigate how legal institutions and characteristics of banking systems affect the provision of trade credit for private firms. The results show that there is more reliance on trade credit versus short‐term bank financing in environments characterized by higher legal enforcement while protection of creditors’ rights has no effect on the relative use of trade credit. As for the influence of the structure of the banking system, the relative use of trade credit, compared to short‐term debt, increases with the weight of bank financing in the country and the existence of restrictions on banks owning and controlling nonfinancial firms. During the global financial crisis, the relative use of trade credit increased, compared to short‐term debt, while it decreased during the COVID‐19 pandemic.